Rancang Bangun Sistem Informasi Administrasi Vaksinasi Meningitis Berbasis Web di Kantor Kesehatan Pelabuhan Kelas III Banda Aceh - Dedi Apriyandi; Kusworo Adi; Aris Puji Widodo (Jurnal Manajemen Kesehatan Indonesia, 2017)
Meningitis vaccination service in Polyclinic of Class III Port Health Office (KKP) of Banda Aceh almost annually has increased the number of patients. There are several problems in the administration information system of meningitis vaccination that is currently running which officer is taking a long time to monitor the stock of vaccine and searching patient’s data that has been vaccinated. In the other hand, the data and information produced has yet incomplete, inaccurate and inconforn according within user system problems, Inaccurate timing for reporting and resulted to the inforrmation’s inconsistency. The purpose of this research is to produce an web-based information system of vaccine administration of meningitis at Polyclinic Class III Port Health Office of Banda Aceh.     The type of researchs used are qualitative and quantitative. This research design using one group pre and post test, system development using FAST method (Framework for the Application of System Techniques). Research subjects consisted of 8 respondents who work in Polyclinic Port Health Office Banda Aceh. The result of observation and interview is conducted by the method of content analysis and descriptive analysis by using the weighted average. Descriptively, the results of data analysis shows which overall weighted average value of quality information before the development of 1.91 system and after the development of 3.64 system with a difference of 1.73. The average calculation of time required to perform services to patients to be faster 4.9 minutes.     There is need support and commitment from the Class III Port Health Office Banda Aceh for implementing the administration information system of meningitis vaccination that has been developed optimally. Monitoring and evaluating users of the system should be performed periodically by Port Helath Office of Banda Aceh.